Removal of crystal violate dye from aqueous solution by adsorption on mixture of activated carbon: A kinetic & equilibrium study - Wagh, Prakash Bhila; Shrivastava, V.S; Shrivastava, V.S (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Â The kinetics and equilibrium study of crystal violate dye adsorption on mixture of activated carbon (PWCAC) and (CSAC) was studied. The use of low cost ecofriendly adsorbent has been investigated as an ideal alternative to the current expensive methods of removing of dye from aqueous solution. This study was done by batch adsorption techniques. The quantitative adsorption kinetic and equilibrium parameter for crystal violate dye were studied using uv-visible adsorption spectroscopy. The effect of initial dye concentration, pH,adsorbent dose, temperature, particle size were determined to find the optimal condition for adsorption. The percentage removal of dye was found to be most effective at pH10and contact time 120 min and at an adsorbent dose 4 g/L of dye. The study indicates thatâ€™s, the percentage removal of dye increases with increasing initial dye concentration, adsorption dose and contact time and attains equilibrium at optimum conditions. The equilibrium study of adsorption of crystal violate dye on to mixture of activated carbon was investigated using pseudo first order and pseudo second order kinetic models. The adsorption kinetics was found to follow pseudo second order kinetic model. The equilibrium adsorption data of crystal violate dye on PWCAC and CSAC mixture was analyzed by Langmuir and Freundlich adsorption model. The results show that the Langmuir model provides the best correlation.